Synthesis and Antibacterial Activities of Novel Pyrimidines Derived from 2-Oxo (or Thioxo)-4-Phenyl-5-Carbethoxy-6-Methyl-1,2,3,4-Tetrahydropyrimidine - Foroughifar, N.; Mobinikhaledi, A. (Asian Journal of Chemistry, 2010)
The 2-Oxo (or thioxo)-4-Phenyl-5-carbethoxy-6-methyl-1,2,3,4-tetrahydropyrimidine (1a–c) were prepared. Heating a mixture of (1a–c, X = S) in 1,2-dibromoethane or chloroacetylchloride gave the thiazolopyrimidines (2a–c) and (3a–c) respectively. Acetylation of (1a–c, X = S) with acetic anhydride and acetic acid yielded the products (3a–c). Alkylation of (1a–c, X = S) with alkyl halide in alkaline medium in 1 : 2 and 1 : 1 ratios gave only monoalkyl derivatives (4a–c). Additional proof for the site of substitution was obtained by alternative synthesis of product (6a–c) through methylation of (5a–c). Product (1a, X = O) on acylation and alkylation in (1a–c, X = S) conditions gave structures 7 and 8 respectively, and reaction with POCl3) afforded 3-formyl-2-oxopyrimidine (9) in good yield. Some of these products were screened for antibacterial activity.